Eye reactions under the influence of drugs of abuse as measured by smartphones: a controlled clinical study in healthy volunteers - Kuijpers, Kiki W. K.; Andersson, Karl; Winkvist, Maria; Niesters, Marieke; van Velzen, Monique; Nyberg, Fred; Dahan, Albert; Hämäläinen, Markku D. (Frontiers in Neuroscience, 2025)
BackgroundIt is known that illicit and prescribed drugs impact pupil size, eye movement and function. Still, comprehensive quantitative evaluations under known ambient light conditions are lacking, when smartphones are used for monitoring.MethodsIn this clinical study (NCT05731999), four medicinal products with addiction risks were administered to 48 subjects (18–70 years old, all with informed consent, 12 subjects per drug). Videos captured by smartphones at ~50 lux and ~ 500 lux documented the eye’s reaction before and after controlled intake of single doses of oral oxycodone (20 mg), lorazepam (2 mg), lisdexamphetamine (70 mg) and inhaled cannabis flos (65 mg with 22% THC) over a 5-h test period. Data from three observational tests, non-convergence (NC, ability to cross the eyes), nystagmus (NY), and pupillary light reflex (PLR) were converted into 24 key features that represent different eye characteristics.ResultsOf the acquired data, 87–97% produced key features. At peak drug plasma concentration, oxycodone constricted pupils (p < 0.001); lorazepam induced non-convergence (p < 0.001); lisdexamphetamine induced dilated pupils (p < 0.001), irrespective of ambient light conditions. Inhaled cannabis induced miosis (p = 0.05 at ~50 lux, p = 0.10 at ~500 lux), a reduced light-induced amplitude (p = 0.003 at ~50 lux, p = 0.3 at ~500 lux) and redness of the sclerae (p = 0.14 at ~50 lux, p = 0.007 at ~500 lux). The drug effect lasted at least 5 h (p < 0.005) except for inhaled cannabis (2–3 h, p < 0.05).ConclusionThe ocular response to oxycodone, lorazepam, lisdexamphetamine and cannabis, as measured under controlled light conditions using a smartphone-based assessment, demonstrated distinct and readily distinguishable patterns for each substance.Clinical trial registrationIdentifier, NTC05731999.